산업용 차량의 시야성에 관한 연구 - 최진봉 (The Graduate School, Ajou University, 2006)
As industrial vehicles have been diffused, forklift accidents also tend to increase. More than 80% of these accidents are incurred because the visibility of forklifts is not secured. The main causes that aesthetic appearances of designer and function of relative engineer have mainly considered rather than considerate ergonomic and cognitional engineering design. The purpose of the study is to compare and estimate the visual range of current forklift truck by comparing and contrasting analysis of ISO 13564 regulations and CATIA after measuring the vision view of the front, rear and visual obstacles factors. The results showed that CATIA and Human have the similarities in terms of ISO 13564 measurement standards.
학위논문(석사)--아주대학교 일반대학원 :산업공학과,2006. 8
Keywords: Forklift trucks; Visibility; ISO 13564